Policy Brief—Using Lessons from Reverse Auctions for Renewables to Deliver Energy Storage Capacity: Guidance for Policymakers. (24th January 2019) - Lackner, Maureen; Koller, Steven; Camuzeaux, Jonathan R
Abstract: As renewable technologies grow cheaper, intermittency is emerging as a critical challenge for achieving large-scale renewables deployment in the electric power sector. Energy storage is particularly well suited to help integrate renewables into the power sector's energy mix because of its ability to store excess energy when prices are low, which can then be discharged when prices are high (i.e., energy arbitrage). Based on recent literature, existing data, and conversations with technical experts, this policy brief explores whether reverse auctions, a market-based tool widely used to procure renewables capacity, might also be cost effective for energy storage procurement. Past experience with renewable energy procurement and early evidence from battery storage systems suggest that reverse auctions are a valuable policy tool for driving down the prices of new storage capacity. However, auction design is important not only for competition and price discovery, but also to encourage the participation of developers of innovative technologies and to guarantee timely delivery of new capacity. In particular, we encourage policymakers to consider the multiple grid services that storage systems can provide in order to ensure that reverse auction frameworks accurately price and capture the value of storage system services in meeting electric power grid demand.